Culture and Complexity: Graffiti on a San Francisco Streetscape - James, Sarah (M/C journal, 2007)
Figure 1 Recently I was walking down a street in The Mission district of San Francisco, which has a high proportion of the city’s Mexican population, when I was struck by a mural on the side of a shop. Vivid and colourful, the mural depicted a large Aztec face surrounded by lush jungle, aesthetically balanced by a carved stone face on the other end of the mural (Figure 1). It was not the beauty, size or colour of the artwork that most impressed me but the way it replicated art I had seen days before walking around Aztec ruins near Mexico City. The paintings I had seen at these pyramids were close to two thousand years old, and this mural, complete with ‘tags’, was created with spray-paint in (probably) the last few years. One was in the ‘traditional home’ of the Aztecs, Mexico, and the other in the Mexican neighbourhood of a neo-colonial American city. However, while one site was celebrating people long since dead, the other a vibrantly alive culture in the cityscape of San Francisco. The migrant, or the diasporic community, is central to many contemporary discussions on the effect of increased globalisation on human cultures and societies (Chambers ). This is not to suggest, however, that globalisation or its impact on human cultures is only a recent phenomenon. Such an assumption implies a sense of amnesia about the processes of migration and diaspora that both instigated, and developed from, processes such as colonisation. San Francisco’s Mexican community do not represent the colonised indigenous people of the United States (US), but they have been affected by a colonial history of their own and the neo-colonialism of the US through processes such as the North American Free Trade Agreement (NAFTA). This rendering, while obviously reductionist, indicates the complex nature of the position of Mexican migrants in San Francisco, and the multiple places, events, histories, countries, politics and policies that shape their journey. The picture of an Aztec face, situated within a largely Mexican neighbourhood, fiercely facing San Francisco presents a number of questions around ideas of culture, hybridity and thirdspace that are connected to theories of complexity. The concept of complexity provides a rich framework through which to engage with themes of culture and hybridity, explored through this symbolic painted presence in the urban landscape. Engagement with complexity theories can illustrate the already present, albeit unarticulated, engagement with complexity in concepts such as cultural hybridity, as well as opening up new ways in which to engage with such ideas. In this paper, I seek to illustrate how complexity can develop concepts in humanities, allowing for a greater exploration and sense of adventure of what is and can be. I will explore the idea of culture and its complexity, and how it can be enriched by complexity. It is an exploration of what can be produced and is emerging rather than the (continued) search for the ‘real’ or an uncovering of bedrock ‘truth’ in social science. As a number of commentators have argued, this idea continues to persist in social science research, despite the apparent changes wrought by poststructuralist thought (Crang, “There Is Nothing”; Crang, “New Orthodoxy”; Lorimer). This article seeks to contribute to current dialogues regarding how theories of complexity might enrich social science research using the concept of culture. The limitations of paper size and breadth of topic shape this article as gesturing towards the possibilities of engaging with the notion of complexity in social science, explored using the symbol of a mural and its location within the Mission District of San Francisco. There are a number of theoretical positions that fall under the notion of complexity; these include chaos theory, catastrophe theory, mathematical complexity and fractals (Manson). From the 1970s, there has been an increasing acceptance and application of complexity theories into social science and popular knowledge, in particular from the late 1990s (Nowotny; Thrift; Manson; Urry, Global Complexity). In my discussion of complexity I am drawing on the translations of these ideas into the domain of social science. I am looking at the disjuncture between cause and effect and the concept of emergence (Thrift; Urry, Global Complexity). These concepts, I argue, can be used to develop areas in the social science such as post-colonial theory that may, at first, seem unrelated. As complexity theory is, well, so complex and really an umbrella term or a "scientific amalgam", it is important to clarify how these theories will be interpreted here (Thrift). Emergence, according to Urry, is the way in which things self-organise over time (Urry, “The Complexities” 33). To expand on this, emergence can be described as the process of self-organisation of things (human and non-human) to create a new entity, an assemblage (Urry, Global Complexity). A central idea of emergence is that complexity is more than ‘complicated’, more than simply the coming together of multiple entities or aspects. The relationship between its parts constitute a new set of entities that make the whole more than the sum of its parts (Urry, Global Complexity; Thrift). It is also the process though which new hybrid entities emerge from this assemblage of previously separate entities. To return to the mural, an analysis of this painting (based on the hypothesis that it has been created by the diaspora from Mexico in San Francisco) would suggest it has emerged through an assemblage of processes of migration, issues of cultural heritage, ideas of authentic tradition, resistance, social inequity, difference and (possibly) a shopkeepers desire for a nice wall. All the known (and unknown) elements, human and non-human, that have (hypothetically) influenced this murals creation do not simply fit together in an equation that automatically results in ‘graffiti art’. Instead it has emerged due to a unique coming together of elements, an assemblage, in a particular time and geographical location. The disjuncture between cause and effect highlighted in a complexity perspective is illustrated here as it is possible to see the process of colonisation of Mexico and the United States has started a chain of events that have lead to the creation of this mural. However, there is no direct line of cause and effect that the act of colonisation would lead to the construction of such a mural. While we can begin to unpack this process in hindsight, the emergent processes that have lead to its creation ensure that such an endeavour will not easily or ever produce a simple equation for its occurrence. Cultural Complexity Social science in many ways relies on the notion that things are not easily analysed, not simply quantifiable or knowable (Dwyer and Limb). The actual language of complexity, however, has generally been missing from such discussions. This absence has limited the ability or, perhaps more accurately, the willingness to articulate logically and rationally what it means to gesture to an unknowingness, to processes of which outcomes cannot be fully predicted or explained (Lorimer; Crang, “There Is Nothing”). It is perhaps only now that it has been ‘validated’ through scientific knowledge such as physics, that we can embrace these ideas explicitly in social science. Using the notion of culture I will illustrate how complexity has been part of social science before it was articulated as such, what complexity theory offers in relation to the social world and how it might be engaged in relation to theory such cultural hybridity. The concept of culture in social science has expanded from the notion of fixed, homogenous ‘way of life’ in a specific geographic space, in early anthropological accounts, to a more complex processual view of culture (Ang, Not Speaking; Couldry). The work of Raymond Williams was seminal in the development of this idea of culture, which continues to be a central aspect of disciplines such as cultural geography and cultural studies (Anderson and Gale; Anderson et al.; Anderson; Ang, “Predicament”; Ang, Not Speaking). This work illustrates the complexities of culture as not only porous and shifting at its boundaries but also internally differentiated so that cultural coherence cannot be assumed (Anderson; Ang, “Predicament”). In terms of complexity theory, the entities that together form a ‘culture’ exist outside of the culture and can in turn work to destabilise and change the culture internally (DeLanda). While recognising that there have always been flows of people, trade and ideas around the world, it has been argued that the current epoch sees these flows at an unprecedented rate (Appadurai; Castells). The level of trans-national migration and movement of people, and the disruption of space and time created by processes of globalisation, further challenge conceptions of culture as fixed or homogenous (Couldry). This expansion of the notion of culture has dual connotations for my reading of the mural. The mural depicts a ‘traditional’ image of Mexican culture before it was affected by contemporary globalisation, but this is being depicted from the position of a diasporic subject in downtown San Francisco. In the painting of this mural it is possible to see the tension between idealisations of more traditional conceptions of a fixed, homogenous culture and the changes wrought on this culture by globalisation. The contrast of the painting’s subject and its location conveys the process of emergence of the (imagined) Mexican-American painter’s hybrid identity. Global Complexity These developments in cultural theory present a complex notion of culture, highlighting the influence of globalisation in creating this complexity. The interjection of complexity theory into social science more recently can enrich these readings of the complexity of cultural systems. It provides an overarching framework through which to organise and